The nonprofit handbook (Wiley, 2001)
he Third Edition of this invaluable handbook provides a complete overview of the entire development function, from management and strategic planning to hands-on, practical guidance for the various kinds of fundraising. Written by leading fund-raising professionals and edited by James M. Greenfield, this volume is a classic in the field of fundraising